FUNGSI DAN PERAN HUMAS DI LEMBAGA PENDIDIKAN - Wina Puspita Sari; Asep Soegiarto (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2019)
AbstractThe demand for quality human resources in order to compete in the ASEAN Economic Community or the ASEAN Free Market is a challenge for educational institutions to continuously improve their quality in preparing human resources with good morals and have competitive advantages. The current development of public relations is quite encouraging. Public relations or public relations is no longer an unfamiliar term. The term is indeed quite popular and has become popular in Indonesia and the public relations profession is now becoming a